Grammarly as Automated Writing Evaluation: Its Effectiveness from EFL Students’ Perceptions - Dewi, Utami (Bina Nusantara University, 2022)
The research aimed to describe EFL students’ perceptions of the effectiveness of Grammarly as an Automated Writing Evaluation (AWE). Nowadays, the Grammarly application is used to give AWE in many EFL writing classes. The respondents of the research were 75 students in an EFL writing class. The questionnaires and interviews were used to explore the students’ perceptions of using Grammarly in editing their drafts. The data from the questionnaires were calculated by percentages, and the data from the interview were analyzed by content analysis. The results show that the students have positive perceptions of using the Grammarly application as AWE. They state many advantages of Grammarly, such as Grammarly helps to identify errors in grammar, punctuation, spelling, and word choices in writing; helps to minimize errors in writing products; to enhance paraphrasing skills; to corrects the errors in writing anytime and anywhere; helps to improve students’ vocabulary; and Grammarly is easier to find errors in writing. Besides the advantages, the students state the drawback of Grammarly as AWE, such as Grammarly for free version has limited features to check errors; Grammarly for the premium version is expensive for students; and Grammarly cannot be accessed offline. The results of the questionnaires and interview represent that the Grammarly application has positive impacts on EFL students as an automated writing evaluation.